Reactivated herpetic gingivostomatitis with secondary herpes-associated erythema multiforme and oral candidiasis post-COVID infection: A case report - Lee, Haeseong; Davoudi, Jouliana; Sedghizadeh, Parish (Journal of Case Reports in Dental Medicine, 2023)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that presents with a multitude of clinical presentations in various body systems. In addition to hematological, radiological, and biochemical findings, oral manifestations of COVID-19, including but not limited to xerostomia, loss of taste, and oral lesions have been reported. To our knowledge, this is the first case to report on a series of multifactorial and concurrent viral, autoimmune, and fungal oral lesions following a COVID-19 infection, namely the reactivation of herpetic gingivostomatitis, herpes-associated erythema multiforme, and concomitant oral candidiasis. This study aims to present a case of compounded immunological involvements of COVID-19 and frame it as a possible predisposing factor to the development of oral lesions and symptoms due to COVID-19’s profound role in immune dysregulation. Further studies are needed to investigate the etiopathogenesis and pathophysiology of the recurrence of oral lesions following COVID-19 infections.